2020
DOI: 10.1101/2020.10.08.20208108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-targeted dose allocation can halve COVID-19 vaccine requirements

Abstract: In anticipation of COVID-19 vaccine deployment, we use an age-structured mathematical model to investigate the benefits of optimizing age-specific dose allocation to suppress SARS-CoV-2 transmission. Across 179 countries, we find that the highest priority individuals are typically those between 30 and 59 years of age because of their high contact rates and higher risk of infection and disease. We reaffirm that vaccination alone may be insufficient to achieve herd immunity in some settings, and that additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 27 publications
(35 reference statements)
1
36
0
Order By: Relevance
“…The social interaction patterns have a significant impact on “risk contacts” in Covid-19, as known from literature 27 , 28 , 29 and again shown in this study. Even imperfect immunity conveyed to a significant proportion of the age groups that fire the pandemic most is therefore highly desirable.…”
Section: Discussionsupporting
confidence: 78%
“…The social interaction patterns have a significant impact on “risk contacts” in Covid-19, as known from literature 27 , 28 , 29 and again shown in this study. Even imperfect immunity conveyed to a significant proportion of the age groups that fire the pandemic most is therefore highly desirable.…”
Section: Discussionsupporting
confidence: 78%
“…Notably, “protecting the vulnerable” is achieved best, when not only the vulnerable, but all population segments are immunized, in particular those that contribute more to drive the pandemic than the elderly 19,20,21 . A large number of infected young people combined with the imperfect protection achievable by vaccination in the elderly still represents a relevant threat to the vulnerable, rendering the strategy focusing on the elderly-first inferior to stopping the pandemic through a comprehensive approach.…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicated that vaccinating school-aged children as well as their parents would be the optimal scenario when vaccine supply is limited in order to indirectly protect others in the community and, thus, reduce the number of severe health outcomes [ 12 , 13 , 15 ]. In the context of COVID-19 vaccination, Meehan et al assumed two distinct modes of action for potential vaccines: those that protect against initial infection and those that reduce the severity of symptoms [ 17 ]. The study by Meehan et al suggested that, in general, individuals aged 30–59 years should receive the highest priority for vaccination because of their high contact rates and high risk of infection [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of COVID-19 vaccination, Meehan et al assumed two distinct modes of action for potential vaccines: those that protect against initial infection and those that reduce the severity of symptoms [ 17 ]. The study by Meehan et al suggested that, in general, individuals aged 30–59 years should receive the highest priority for vaccination because of their high contact rates and high risk of infection [ 17 ]. However, Bubar et al found that in the USA, a transmission-blocking vaccine should be prioritized in younger adults (age 20–49 years) to minimize the cumulative incidence and in people older than 60 years to minimize mortality [ 18 ].…”
Section: Introductionmentioning
confidence: 99%